The intersection of affinity and specificity in the development and optimization of T cell receptor based therapeutics. (December 2018) - Riley, Timothy P.; Baker, Brian M.
Highlights: T cell receptors are central to new immunological therapies. TCRs mediate one of the most complex protein–protein interactions in biology. Intricate selection and signaling mechanisms add additional layers of complexity. We should distinguish TCR molecular recognition from T cell functional recognition. Engineering TCRs can have unpredictable impacts on T cell specificity. Natural immunity and structure-guided design provide lessons for making better TCRs. Abstract: The role of the αβ T cell receptor (TCR) in identifying immunological targets and signaling appropriate responses provides for exciting translational opportunities. Yet TCRs mediate one of the most complex protein–protein interactions in biology, with intricate signaling and selection mechanisms adding additional layers of sophistication. In this review, we discuss how these complexities influence the development and optimization of TCR-based therapeutics, focusing on the intersection between structure, affinity, and specificity. We highlight similarities between TCRs and germline antibodies in molecular recognition, but emphasize that engineering TCRs by mimicking antibody maturation may not translate into improved biological outcomes. A key point is the need to distinguish TCR biochemical recognition from T cell functional recognition and the complications this distinction has for efforts in TCR engineering. We suggest learning from natural immunity and taking advantage of structural features and state-of-the-art protein design principles as a means to optimize TCRs for therapeutic use.